CASP4 can be a diagnostic biomarker and correlated with immune infiltrates in gliomas - Tian, Guopeng; Li, Qiao; Niu, Liang; Luo, Yusong; Wang, Hongyu; Kang, Wei; Fang, Xiang; Bai, Shengwei; Yuan, Guoqiang; Pan, Yawen (Frontiers in Oncology, 2023)
Gliomas are the most common and invasive malignant tumors that originate in the central nervous system. Currently, the primary treatment modality for gliomas is maximum surgical resection, supplemented by radiotherapy and chemotherapy. However, the long-term survival rate has not significantly increased. Pyroptosis is a new form of programmed lytic death that has been recently discovered. Caspase 4 (CASP4) plays a key role in pyroptosis. Many studies have shown that pyroptosis is not only related to inflammation, but is also closely related to the occurrence and development of most tumors. This study aimed to prove CASP4 is a key role in the mechanism of gliomas. We used expression data from The Cancer Genome Atlas and the Chinese Glioma Genome Atlas to explore the relationship between CASP4 expression and glioma prognosis. The differential expression of CASP4 in gliomas and normal tissues was first tested, and then, the connection between CASP4 and tumor prognosis was explored. The relationship between CASP4 expression and immune cell infiltration was also investigated. Finally, the possible pathways were analyzed using Gene Ontology, Kyoto Encyclopedia of Genes and Genomes, and gene set enrichment analysis. CASP4 was highly expressed and associated with a significantly lower survival rate in patients with glioma. It could also influence immune cell infiltration by releasing cytokines. In conclusion, CASP4 can be a diagnostic biomarker and is a promising therapeutic target for gliomas.